Challenges and Prospects of Environmental Compliance and Monitoring in Borno State, Nigeria - Mathias Nzitiri Bwala; Usman Musa Yusuf; Abdulrahman Bukar Usman (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
The continuous misguided use of the environment and its resources has caused several challenges which continue to grow in size and complexity day by day, threatening man’s survival on earth. To tackle environmental issues caused by anthropogenic activities, the government enacted laws at national and international levels aimed at preserving, conserving, and protecting the environment. This paper seeks to assess the challenges and prospects of compliance with environmental laws, policies, and regulations in Borno State, Nigeria. A questionnaire was designed and administered to government environmental law enforcement establishments (NESREA and BOSEPA), cooperate bodies, and civil societies. 152 questionnaires were retrieved and used for the study. Data were analyzed using Statistical Package for Social Sciences (SPSS) and presented in tables and charts. The study reveals a low level of compliance with environmental regulations in the study area. Individuals and cooperative bodies comply with environmental laws, policies, and regulations only when compelled by government agencies. The study proffers the following measures to enhance environmental compliance: legislative empowerment of enforcement agencies to sanction violators, grievous sanctions to violators, proper funding of enforcement agencies, Improvement of staff welfare, development of compliance monitoring feedback systems, employment of qualified staff, and provision of adequate infrastructure.